2017
DOI: 10.1002/2016ja023724
|View full text |Cite
|
Sign up to set email alerts
|

F3 layer development during quiet and disturbed periods as observed at conjugate locations in Brazil: The role of the meridional wind

Abstract: In this work we use ionospheric data from two low‐latitude stations located north and south of the geomagnetic equator, at approximately the same magnetic longitude, in order to study the occurrence of the F3 layer. The location of the stations being at almost geomagnetically conjugate points is such that the effects of the electric field/vertical plasma drift and diffusion will be almost symmetric around the magnetic equator. Under this configuration it is possible to deduce the effect of meridional wind in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 53 publications
4
33
0
Order By: Relevance
“…The additional stratification of F 3 layer due to PPEF in the dayside equatorial region has been observed earlier by Balan et al [2008] andTulasi Ram et al [2012]. The F 3 layer occurrence characteristics during storm time and their comparison with those of quiet time are reported by Batista et al [2017]. The enhanced electric fields transport the equatorial plasma vertically upward; however, Brazilian sector being in dayside, the ion production viz photoionization continuously occurs at F region base around 200 km.…”
Section: 1002/2017ja024009mentioning
confidence: 73%
“…The additional stratification of F 3 layer due to PPEF in the dayside equatorial region has been observed earlier by Balan et al [2008] andTulasi Ram et al [2012]. The F 3 layer occurrence characteristics during storm time and their comparison with those of quiet time are reported by Batista et al [2017]. The enhanced electric fields transport the equatorial plasma vertically upward; however, Brazilian sector being in dayside, the ion production viz photoionization continuously occurs at F region base around 200 km.…”
Section: 1002/2017ja024009mentioning
confidence: 73%
“…Balan et al () have shown the F 3 layer occurrence at three stations spanning from the equator to southern low‐latitudes of 11.6°S. Later, Batista et al () presented the F 3 layer occurrence at two conjugate stations at 9.7°N and 13.3°S dip latitudes. In general, the F 3 layer occurrences over equatorial latitudes during storm times are explained due to rapid uplift of F layer by eastward PPEF owing to the southward turning of IMF B z .…”
Section: Resultsmentioning
confidence: 98%
“…Under normal E × B vertical drift and usual photochemical and dynamical processes, the northward EMW during winter pushes the plasma upward along the magnetic field lines at the Southern Hemisphere preventing effective diffusion process and retaining part of the ionization at higher altitudes to result in higher B0 closer to the magnetic equator in the Southern Hemisphere. Oppositely, the southward EMW during summer pushes the plasma upward along the magnetic field lines at the Northern Hemisphere to manifest higher B0 nearer to the magnetic equator in the Northern Hemisphere (Balan et al, ; Batista et al, ; Tulasi Ram, Su, & Liu, ). During equinox, the transequator EMW is incompetent and hence regular equatorial phenomena control the double crest structure in B0 that is barely noticed only during LSA equinox and disappears during HSA equinox in our study.…”
Section: Equatorial and Low‐latitude Features Of Bottomside Profile Pmentioning
confidence: 99%